Revisiting the Academic Hardiness Scale: Revision and Revalidation. (November 2013) - Creed, Peter A.; Conlon, Elizabeth G.; Dhaliwal, Kamal
We used two studies to evaluate, modify, and provide initial validation for a revised Academic Hardiness scale. First, 16 experts rated scale items for content validity and identified two problematic questions. Second, confirmatory factor analyses with 300 Grade 10 students (46% boys, age range 14–17) identified a 17-item version to be the best fit. Construct validity was demonstrated by testing correlations between this revised scale and academic achievement (spelling, reading, and mathematics) and student self-evaluations (competencies, self-efficacy, and self-worth). Predictive validity was supported by showing that the scale differentiated between students who enrolled in academic and nonacademic streams, and differentiated between students who completed their course and those who did not. We failed to identify a second-order factor for hardiness, suggesting (a) that hardiness should be interpreted at the subscale, rather than at the global level, and (b) that the hardiness construct might need to be reconsidered for adolescents.